دور الدين في المجتمع العربي التقليدي - فرحات, نادية (University of Eloued جامعة الوادي, 2018)
إن الحديث عن الدين كظاهرة اجتماعية يقودنا إلى فكر إميل دوركا يم عند دراسته للمجتمعات البدائية أين استخدم الدين من قبل جماعة صغيرة للسيطرة على كل فئات المجتمع، والأصل أن الدين شريعة سماوية انزله الله لتنظيم علاقات الإنسان بالأخر للحفاظ على حقوق كل واحد وأمنه وسلامته بهدف إنشاء مجتمع سليم وسوي خالي من مختلف الآفات والعلل، إلا أن الواقع يعكس نظرية دوركا يم في استخدامه للسيطرة على الأخر وإخضاعه لتحقيق أهداف ومصالح خاصة تتنافى كلية مع أهداف الدين وغاياته في المجتمع. Abstract : The role of religion in traditional Arab society Speaking about religion as a social phenomenon leads us to the thought of Emile Durkheim when he studied primitive societies where religion was used by small groups to control all groups of society. Originally, religion is a heavenly law sent down by God to regulate human relations with each other to safeguard the rights, security and integrity of everyone. Free of various scourges and misfortunes, but reality reflects the Durkheim theory in the use of religion to control and dominate others for achieving special goals and interests are completely incompatible with the objectives of religion and its role in society.
The role of religion in traditional Arab society
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 04 جامعة الوادي
Keywords: الدين، ادة السيطرة، اداة تبريرية، الظاهرة الاجتماعية; Religion; Traditional; Arab Society